Re-presenting feminist methodologies : interdisciplinary explorations - Kalpana Kannabiran Ed.; Padmini Swaminathan Ed. (London : Routledge, 2020)
This book tracks the trajectory of gender in the social sciences and humanities through an exploration of the challenges and contradictions that confront contemporary feminist analysis as well as future directions. Drawing on research in India, the essays in the volume engage with the subject in imaginative ways, each one going beyond documenting the persistence of gender inequality, instead raising new questions and dilemmas while unravelling the complexities of the terrain. They also interrogate extant knowledge that has 'constructed' women as 'agentless' over the years, incapable of contesting or transforming social orders - by taking a close look at gendered decision-making processes and outcomes, sex for pleasure, health care practices, content and context of formal schooling or the developmental state that 'mainstreams' gender. Do existing feminist methodologies enable the understanding of emerging themes as online sexual politics, transnational surrogacy or masculinist 'anti-feminist' sensibilities? The feminist methodologies delineated here will provide readers with a toolkit to assess the criticality of gender as well as its nuances. The work foregrounds the importance of intersectionality and builds a case for context-specific articulations of gender and societies that destabilize binary universals. This volume will be useful to scholars and researchers across the disciplines of the social sciences and humanities, especially gender studies, women's studies, feminism, research methodology, education, sociology, political science and public policy.
Introduction: Re-presenting Feminist Methodologies -- Part One: Mapping Terrains -- Section 1: Feminist Journeys -- 1. Studying Women and the Women's Movement in India: Methods and Impressions -- 2. 'To bounce like a ball that has been hit': Feminist Reflections on the Family -- 3. Masculinities in Fieldwork: Notes on Feminist Methodology -- 4. Real Life Methods: Feminist Explorations of Segregation in Delhi -- Section 2: Unpacking Disciplines -- 5. Stories We Tell: Feminism, Science, Methodology -- 6. Researching Online Worlds through a Feminist Lens: Text, Context and Assemblages -- 7. The Erotics of Risk: Feminism and the Humanities in flagrante delicto -- 8. Impractical Topics, Practical Fields: Notes on Researching Sexual Violence in India -- Part Two: Exploring Themes -- Section 3: Development -- 9. Planning for Modernization? Feminist Readings of Plans and Planned Development in India -- 10. Unpacking 'Win-Win': How Feminists Interrogate Microfinance -- 11. Globalisations, Mobility and Agency: Understanding Women's Lives Through Women's Voices -- 12. 'Ladkiyaan Phir Aage?': Towards Understanding the Formal School System -- Section 4: Health -- 13. Researching Assisted Conception from a Feminist Lens -- 14. RUWSEC Clinic: Challenges posed by the medical establishment to an attempt at a grassroots feminist clinic -- 15. Feminist Critical Medical Anthropology Methodologies: Understanding Gender and Healthcare in India.
"A Routledge India Original"--Cover.
Includes bibliographical references and index.
Keywords: Gender identity -- India; Women -- India; Gender mainstreaming -- India; Gender identity; Gender mainstreaming; Women